Integrasi Ilmu Agama Dan Sains Dalam Pendidikan Islam Kontemporer - Humairoh, Ayu Savana; Mustafidin, Ahmad (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
In the era of globalization and rapid technological advances, Islamic education faces the challenge of remaining relevant without losing its scientific identity. Integration between religious knowledge and science is one strategic approach in responding to this challenge. This article discusses the urgency, concept, and implementation of the integration of religious knowledge and science in contemporary Islamic education. This approach not only aims to eliminate the dichotomy between revealed knowledge and rational knowledge, but also to form holistic learners, namely those with spiritual, intellectual, and social intelligence. The results of the study show that the integration of religious knowledge and science can enrich the Islamic education curriculum, strengthen the values ​​of faith in the learning process, and produce graduates who are able to compete globally without letting go of the roots of Islamic values. The active role of educational institutions, an integrated curriculum, and educators who have interdisciplinary competence are needed to realize this integration effectively.